2021
DOI: 10.1186/s13020-021-00485-4
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids on diabetic nephropathy: advances and therapeutic opportunities

Abstract: With the advances in biomedical technologies, natural products have attracted substantial public attention in the area of drug discovery. Flavonoids are a class of active natural products with a wide range of pharmacological effects that are used for the treatment of several diseases, in particular chronic metabolic diseases. Diabetic nephropathy is a complication of diabetes with a particularly complicated pathological mechanism that affects at least 30% of diabetic patients and represents a great burden on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 134 publications
1
19
0
Order By: Relevance
“…Despite the enormous advances on cardiovascular and renal protection provided by the SGLT2i and GLP-1 RA introduced in clinical practice for diabetic patients [ 15 , 16 , 17 ], no drug targeting inflammation and redox balance signaling pathways, key elements in the genesis and progression of DN [ 7 , 18 ], is available so far. Flavonoid compounds seem to be a promising alternative to treat chronic DM complications due to their outstanding pharmacological effects including anti-inflammatory, antioxidant, antidiabetic, and antihypertensive, as evinced in experimental models and clinical studies [ 20 , 33 , 34 ]. The synthetic flavonoid hidrosmin, a diosmin-derived flavone with vasoprotective effects [ 35 ], is a venotonic agent used for many years in patients suffering from chronic venous insufficiency mainly due to its antiedematous properties and other beneficial effects (i.e., in swelling and leg cramps), more effective in some cases than diosmin [ 21 , 36 ]; however, the therapeutic effects of hidrosmin in other chronic diseases remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the enormous advances on cardiovascular and renal protection provided by the SGLT2i and GLP-1 RA introduced in clinical practice for diabetic patients [ 15 , 16 , 17 ], no drug targeting inflammation and redox balance signaling pathways, key elements in the genesis and progression of DN [ 7 , 18 ], is available so far. Flavonoid compounds seem to be a promising alternative to treat chronic DM complications due to their outstanding pharmacological effects including anti-inflammatory, antioxidant, antidiabetic, and antihypertensive, as evinced in experimental models and clinical studies [ 20 , 33 , 34 ]. The synthetic flavonoid hidrosmin, a diosmin-derived flavone with vasoprotective effects [ 35 ], is a venotonic agent used for many years in patients suffering from chronic venous insufficiency mainly due to its antiedematous properties and other beneficial effects (i.e., in swelling and leg cramps), more effective in some cases than diosmin [ 21 , 36 ]; however, the therapeutic effects of hidrosmin in other chronic diseases remains to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…anticancer mechanisms (Hosseini et al 2021). Quercetin is known to relieve diabetic nephropathy by inhibiting inflammatory and oxidative stress inflammatory pathways (Hu et al 2021). Meanwhile, some studies have also demonstrated that quercetin exerted a nephroprotective effect by regulating macrophage polarization (Lu et al 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Meanwhile, some studies have also demonstrated that quercetin exerted a nephroprotective effect by regulating macrophage polarization (Lu et al 2018). Kaempferol as well has been demonstrated to have a nephroprotective effect through its anti-inflammatory and antioxidant action (Hu et al 2021).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It possesses many biological roles, while in DKD, it shows an anti-fibrotic and antioxidant effect, the last one in an NRF2 partially dependent pathway [ 165 , 166 ]. Other representatives that can trigger the NRF2/KEAP1/ARE pathway are Diphlorethohydroxycarmalol, derived from Ishige okamurae, a species of algae [ 167 ], Genistein [ 6 ], Hesperetin [ 168 ], Myricetin [ 169 ] and Digitoflavone (3,0,4,5,7-tetrahydroxyflavone) [ 170 , 171 ]. Further, some potential NRF2 activators that are part of the same family have been studied in DKD, with promising results, such as Auricularia cornea [ 172 ].…”
Section: Therapeutic Approaches In Diabetic Kidney Disease Via Oxidat...mentioning
confidence: 99%